Expression from engineered Escherichia coli chromosome and crystallographic study of archaeal N, N′‐diacetylchitobiose deacetylase. (28th April 2014) - Mine, Shouhei; Niiyama, Mayumi; Hashimoto, Wakana; Ikegami, Takahisa; Koma, Daisuke; Ohmoto, Takashi; Fukuda, Yohta; Inoue, Tsuyoshi; Abe, Yoshito; Ueda, Tadashi; Morita, Junji; Uegaki, Koichi; et al.
<x xml:space="preserve">Abstract</x> In order to develop a structure‐based understanding of the chitinolytic pathway in hyperthermophilic Pyrococcus species, we performed crystallographic studies on N, N′‐diacetylchitobiose deacetylases (Dacs) from Pyrococcus horikoshii (Ph‐Dac) and Pyrococcus furiosus (Pf‐Dac). Neither Ph‐Dac nor Pf‐Dac was expressed in the soluble fraction of Escherichia coli harboring the expression plasmid. However, insertion of the target genes into the chromosome of E. coli yielded the soluble recombinant protein. The purified Pyrococcus Dacs were active and thermostable up to 85 °C. The crystal structures of Ph‐Dac and Pf‐Dac were determined at resolutions of 2.0 Å and 1.54 Å, respectively. The Pyrococcus Dac forms a hexamer composed of two trimers. These Dacs are characterized by an intermolecular cleft, which is formed by two polypeptides in the trimeric assembly. In Ph‐Dac, catalytic Zn situated at the end of the cleft is coordinated by three side chain ligands from His44, Asp47, and His155, and by a phosphate ion derived from the crystallization reservoir solution. We considered that the bound phosphate mimicked the tetrahedral oxyanion, which is an intermediate of hydrolysis of the N‐acetyl group, and proposed an appropriate reaction mechanism. In the proposed mechanism, the Nε atom of His264 (from the adjacent polypeptide in the Ph‐Dac sequence) is directly involved in the stabilization of the oxyanion intermediate. Mutation analysis also indicated that His264 was essential to the catalysis. These factors give the archaeal Dacs an unprecedented active site architecture a Zn‐dependent deacetylases. Database Structural data are available in the Protein Data Bank database under accession numbers 3WL3, 3WL4, and 3WE7. Structured digital abstract Ph-Dac and Ph-Dac bind by x-ray crystallography (View interaction) Pf-Dac and Pf-Dac bind by x-ray crystallography (View interaction)